Application of intraluminal brachytherapy for malignant obstruction in the porta hepatis: a retrospective control study - Zhang, Yi; Yang, Yang; Li, Lingling; Li, Peimin (Frontiers in Oncology, 2025)
Purpose and backgroundMalignant obstructions in the porta hepatis mainly include malignant obstructive jaundice (MOJ) and portal vein tumor thrombus (PVTT). Stent placement has been one of the most commonly recommended methods to alleviate the physical suffering of these patients, but the long-term outcome has been frustrating in terms of stent occlusion. The aim of this study was to discuss the clinical effect and technical feasibility of intraluminal brachytherapy (ILBT) in patients with malignant obstruction in the porta hepatisMethods and materialsFrom 2016 to 2018, 68 patients diagnosed with malignant obstruction in the porta hepatis were retrospectively included in this study. Twenty-eight patients (group A) received stent placement with iodine-125 seed-strand implantation, and 40 patients (group B) received stent placement only. All patients underwent numerous transarterial chemoembolizations (TACE) after stent implantation. All patients were followed up until death. Clinical data, stent patency and survival time were recorded for further analysis.ResultsThere was no significant difference between the two groups in terms of length of malignant obstruction and baseline characteristics. 68 stents were successfully implanted in both groups.Iodine-125 seed strands were successfully deployed and completely covered the length of the stent in group A. Liver function and jaundice improved continuously in the first 9 months after treatment (P<0.05). Compared to group B, the mean stent patency time was significantly longer in group A (5.5 ± 2.09 months versus 6.86 ± 1.82 months, P<0.001). The mean survival time is longer in group A than in patients in group B (10.03 ± 3.04 months VS 7 ± 2.44 months, P<0.001).ConclusionILBT in combination with stent implantation and TACE has proven to be a feasible and effective palliative treatment to maintain stent patency in patients with PVTT and MOJ.